The EPICure study: associations and antecedents of neurological and developmental disability at 30 months of age following extremely preterm birth - Wood, N (BMJ Group, 2005)
Aims: To describe perinatal factors associated with later morbidity among extremely preterm children at 30 months of age corrected for prematurity. Population: Of 308 surviving children born at ⩽25 weeks gestation in the United Kingdom and Ireland from March to December 1995, 283 (92%) were evaluated at 30 months of age corrected for prematurity. Methods: Cerebral palsy, severe motor disability, and Bayley scores were used as dependent variables in sequential multiple regression analyses to identify factors associated with adverse outcomes. Results: Adverse outcomes were consistently more common in boys. Factors related to perinatal illness, ultrasound evidence of brain injury, and treatment (particularly postnatal steroids) were associated with adverse motor outcomes (cerebral palsy, disability or Bayley psychomotor development index). Increasing duration of postnatal steroid treatment was associated with poor motor outcomes. A score was developed for severe motor disability with good negative predictive value. In contrast, mental development was associated with a broader range of factors: ethnic group, maternal educational level, the use of antenatal steroids, and prolonged rupture of membranes in addition to chronic lung disease. Conclusion: Male sex is a pervasive risk factor for poor outcome at extremely low gestations. Avoidable or effective treatment factors are identified, which may indicate the potential for improving outcome.